(Y1-xNdx)3Zr5O14.5 solid solutions as inert matrices: Phase evolution, order-disorder dynamics and thermophysical behavior. (June 2021) - Bhandari, Koushik; Grover, V.; Roy, Anushree; Bhatt, Ranu; Banerjee, Joydipta; Tyagi, A.K.
Highlights: (Y1-x Ndx )3 Zr5 O14.5 system studied to mimic heavy-loaded minor actinides substituted zirconia. About 60 mol% solubility of Nd 3+ as analysed by XRD shows F-type structure; biphasicity confirmed by EDS. Lattice parameters increase with Nd 3+ -content in defect fluorite systems. Pyrochlore-type micro-domains revealed 50 mol% Nd 3+ onwards by Raman spectroscopy. Thermal conductivity trend with composition bears implication of the hidden local ordering. Abstract: In order to understand structural implications of higher loading of minor actinides (MA) in zirconia-based materials for transmutation, substitution of Nd 3+ in Y3 Zr5 O14.5 has been explored. Nd 3+ is surrogate for minor actinides (Am 3+, Cm 3+ ). Various compositions in (Y1-x Ndx )3 Zr5 O14.5 (0 ≤ x ≤ 1.0) system have been synthesized by high temperature route. The X-ray diffraction studies established end members Y3 Zr5 O14.5 and Nd3 Zr5 O14.5 as defect fluorite (F) and non-stoichiometric pyrochlore-type (P), respectively. The defect fluorite persisted till 60 mol% Nd 3+ -substitution followed by biphasic phase field in F and P- type phases. Interestingly, the Raman spectra revealed the onset of localized pyrochlore-type superstructure much earlier (after 40 mol% Nd 3+ ). Thermal diffusivity of representative nominal compositions were obtained by Laser Flash Technique. Nd 3+ -substitution lowered the thermal conductivity of stabilized zirconia due to additional scattering centres introduced. The work highlights implications of hidden ordered structural features on thermal conductivity trends, which has significance for increasing MA loading.